Ownership and debt financing: Indonesia evidence - Haron, Razali (InTechOpen, 2017)
This study examines whether ownership concentration influences debt financing of firms in Indonesia. Known to be dominated by family owned, firms in Indonesia seem to have certain distinctive characteristics that are evidenced to have significant impact on their debt financing. Apart from the common firm-level determinants, ownership concentration does play an important role in determining the level of debt consumption of the firms. It is revealed that ownership concentration impacts the debt financing positively, reflecting the power and authority of the large controlling shareholders in using debt as controlling mechanism on the entrenched managers. The positive relation-ship may also be explained by the reluctance of large shareholders to engage with equity financing as to avoid ownership dilution and thus can maintain the control of the firms. In terms of ownership identity, however, family firms in Indonesia seem to consume much lesser debt level due to the alignment of interest between shareholders and managers, which makes issuing debts as manager’s disciplinary tool less crucial for family-owned firms. This study contributes to the literature by offering insights on how ownership concentration and family-owned firms decide on their capital structure and how certain distinctive characteristics of the firms influence the financing decision.